A Separation‐Sensing Platform Performing Accurate Diagnosis of Jaundice in Complex Biological Tear Fluids. (1st June 2022) - Zhao, Weidong; Li, Jinming; Xue, Zhenjie; Qiao, Xuezhi; Li, Ailin; Chen, Xiangyu; Feng, Yun; Yang, Zhou; Wang, Tie
Abstract: The detection of biomarkers in tears has aroused great interest owing to the advantages of non‐invasive and rapid collection. The combination of ultrasensitivity and label‐free detection of surface‐enhanced Raman spectroscopy (SERS) sensors is expected to achieve real‐time diagnosis in home medical care. However, the surface of SERS sensors is susceptible to biofouling and inactivation by biological impurities in tears, resulting in rapid degradation of sensitivity, limiting the commercialization of point‐of‐care devices. Herein, a binary nanosphere array with dual properties is constructed as a separation‐sensing platform for the diagnosis of target molecules in tears. The upper part of the structure is composed of Au nanoparticles (AuNPs) and a sputtering Au layer, which can bind the target molecules that interact with Au and provide high‐strength and high‐density SERS hotspots. The lower half is an inactive SiO2 nanosphere array with periodic large pores that allows biological impurities to penetrate the lower part and be separated from the target analyte. Furthermore, this substrate was integrated into homemade tear kits, enabling simultaneous tear collection, pre‐separation, and detection. Combined with the Raman spectra of tears and LDA analysis, we successfully identified patients with jaundice in clinics. This platform is expected to provide an opportunity for early disease screening based on biological fluids. Abstract : An SiO2 @Au@AuNPs substrate was constructed as a separation sensing platform. This separation performance depends on the pore size. Three types of diffusion occur, including interception, single‐file diffusion and Fickian diffusion. This structure was integrated into a home‐made tear assay kit for the diagnosis of jaundice.